Hypercalcemic Pancreatitis: A Rare Type of Acute Pancreatitis Caused by a Parathyroid Adenoma - Rizkou, Jihane; Aouroud, Hala; Handa, Acila; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Acute pancreatitis is an inflammatory process with multiple etiologies, dominated by biliary lithiasis and alcohol consumption. Primary hyperparathyroidism (PHPT) with subsequent hypercalcemia as a cause of acute pancreatitis is very rare and frequently overlooked and serum calcium level plays a key role in the pathogenesis. Here we present a case of 53 years old female with hypercalcemic acute pancreatitis resulted from primary hyperparathyroidism caused by a left parathyroid adenoma.